ARGUING THE NEED FOR QUALITATIVE EXPLORATION IN THE FIELD OF EMERGING DIGITAL PATHOLOGIES - JOHNSON, NICOLA F. (Studia Psychologica: Theoria et praxis, 2015)
Little has been done globally to ethnographically (and holistically) study and understand the lives of heavy Internet users, with insufficient qualitative research (that is, exploratory, descriptive, inductive) published throughout the world. This article presents the findings from qualitative semi-structured interviews with five psychologists, who were asked about their understanding of addiction and Problematic Internet Use. The findings demonstrate the complexity of the field and the possibility of co-morbidity, suggesting that so-called “Internet abuse” or multiple derivatives of the label are inaccurate and unhelpful. In-depth qualitative research is needed to add depth and insight to this highly topical area, where a myriad of scales are being put forward, tested and validated from one hegemonic paradigm within this field. Further nuanced understandings of Internet use need to be developed to work towards constructing theories and pedagogies that help to understand and address digital pathologies successfully.